POTENTIAL EARTHQUAKE HAZARD MICROZONATIONS OF THE JAKARTA CITY - Asdani Soehaimi (Jurnal Geologi dan Sumberdaya Mineral, 2009)
Jakarta, the capital city of the Republic of Indonesia, is a potential earthquake hazard area. The city lies on the very thick ( >294 M ) Quaternary sediments. Destructive earthquakes influenced this city were generated from the subduction and active faults with the Maximum intensity of VI - VII MMI. A microtremor investigation to the shallow soft Quaternary sediment results in the dominant period of 0.05 – 0.85. The classification of this dominant period is the basic classification of rock and soil site and as an important factor of the earthquake hazard susceptibility in a region. Dynamic site responses, which are presented by the multiply of amplification factors and natural dominant periods of this city are divided into five microzonations, these are :–         Very high susceptibility microzonation (index's > 10), covers the area of 7.58 km2  or 1.15 % of the total region of Jakarta occupies a small area of North Jakarta.–         High susceptibility microzonation (index's 7.5 – 10 ), covers the area of 18 km2 or 2.73% of the total region of Jakarta consisting of small area of North Jakarta city (Kapuk resort), Central Jakarta including the area of Setiabudi.–         Moderately susceptibility microzonation (index's 5-7.5), covers the areas of 86.59 km2 or 13.11 % of the total region of Jakarta, including the North, Central, East and South Jakarta and the small area of West Jakarta .–         Low susceptibility microzonation (index's 2.5 - 5), covers the area of 324 km2 or 49.18 % of the total region of Jakarta, and it occupies the western part of North Jakarta, eastern part of west Jakarta and the central part of central Jakarta.–         Very low susceptibility microzonation (index's < 2.5 ), covers the area of 223.47 km2 or 33.83 % of th total region of Jakarta , the area includes a small part of the central Jakarta and the eastern part of west Jakarta.These earthquake hazard microzonations are one of important data base for regional planning in order to mitigate earthquake hazards and risks of the Jakarta city. Keywords: Earthquake hazard microzonation and regional planning